2011
DOI: 10.1111/j.1742-4658.2011.08428.x
|View full text |Cite
|
Sign up to set email alerts
|

PP3 forms stable tetrameric structures through hydrophobic interactions via the C‐terminal amphipathic helix and undergoes reversible thermal dissociation and denaturation

Abstract: The milk protein proteose peptone component 3 (PP3), also called lactophorin, is a small phosphoglycoprotein that is expressed exclusively in lactating mammary tissue. The C-terminal part of the protein contains an amphipathic helix, which, upon proteolytic liberation, shows antibacterial activity. Previous studies indicate that PP3 forms multimeric structures and inhibits lipolysis in milk. PP3 is the principal component of the proteose peptone fraction of milk. This fraction is obtained by heating and acidif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…The PP3 preferentially remains in multimeric structures of 4 to 10 times higher molar mass than its monomeric form. The molar mass of isolated multimeric PP3 fraction were reported to be 1.9 −2.3 × 10 5 g/mol (Sørensen et al, 1997;Pedersen et al, 2012), which were similar to the molar mass of the protein fraction co-isolated with EPS in our study (Figure 5).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The PP3 preferentially remains in multimeric structures of 4 to 10 times higher molar mass than its monomeric form. The molar mass of isolated multimeric PP3 fraction were reported to be 1.9 −2.3 × 10 5 g/mol (Sørensen et al, 1997;Pedersen et al, 2012), which were similar to the molar mass of the protein fraction co-isolated with EPS in our study (Figure 5).…”
Section: Discussionsupporting
confidence: 86%
“…The most abundant contaminant, PP3, also called lactophorin, or glycosylation-dependent cell adhesion molecule-1 (GlyCAM-1), is one of the components of the proteose peptone fraction of milk. Bovine milk contains about 1 g/L of proteose peptone fraction, including ~25% (200-300 mg/L) PP3 (Pedersen et al, 2012). The PP3 is composed of 135 AA residues and is highly soluble in water, as it is highly glycosylated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the slow foaming attitude of M1 samples could be related to the higher presence of PP in which, probably, the PP3 component was not in prevalence. PP3 is expressed exclusively in mammary tissue of ruminants and it is not formed after the milk ejection (Pedersen et al, 2011). Several studies showed that bovine PP3 is a good substrate for PL that reduces the lactophorin to a shorter fragment (residue 54-135) that has lost the emulsifying properties (Sørensen and Petersen, 1993).…”
Section: Proteose-peptone and Milk Foammentioning
confidence: 99%
“…RAD51 has been reported to be associated with bovine oocytes meiosis progress [49,50]. Some candidate genes (e.g., LAP3, GLYCAM1, PDE1B, MICALL2, NPC1) are related with other economically-important traits in cattle such as milk production, carcass traits, body weight, body height, and body length [51][52][53][54][55]. Additionally, several genes were annotated to be associated with stress response in cattle.…”
Section: Candidate Genomic Regions For the Intercepts And Slopesmentioning
confidence: 99%